Effect of Trimetazidine on Myocardial Disorders in Rats - Hadeel Jabar Neama Almuoswi (Journal of Global Pharma Technology, 2019)
Cardiac muscle anemia affects the functions of mitochondria that results in ion disparity. The condition called cardiac arrhythmia. The research aims to study the effect of antianginal medication of trimetazidine on myocardial disorders in rats. The study was conducted on the rats. They were fed with 10 mg trimetazidine per Kg weight of mice each day for seven days. Tests were done for the effect of the moderator on mitochondrial metabolism in severe cardiac muscle anemia affected rats. Acute cardiac muscle anemia results in an injury to mitochondrial functions. So, when anemia cluster without trimetazidine treatment was observed, a major reduction within the infarction range was ascertained in trimetazidine-treated anemia cluster (31±3% vs. 52.8±4.89%). Trimetazidine maintained the mitochondrial organization. And, thus, better the metabolic process management, magnitude relation, and sophisticated activity. Moreover, the mitochondrial biosynthesis and division or fusion of the cells improved. The indubitable Promote the activated receptor gamma peroxisome proliferators (PPARγ), the Joint Co-1α (PGC-1α), mitofusins one (Mfn1), dynamin-related super molecule one (Drp1), Optic nerve atrophy one (OPA1) emerge in rats with acute cardiac muscle anemia. Therefore, the incontestable heart defending effects of trimetazidine was shown to preserve mitochondrial metabolic process, increased biogenesis, and split/union of cells. And, thus, this rat model of cardiac muscle anemia may be effectively used along with other cardio protective agents.Keywords: Trimetazidine, Myocardial disorders, Rats.